Perception of mothers towards expressed breastfeeding at Kamuzu Central Hospital (Peadiatric ward A-Nursery - Bwanali, Lizzie (Kamuzu University of Health Sciences, 2022)
This is a qualitative, phenomenological descriptive study which will be conducted to find out the perception of mothers towards expressed breastfeeding at Kamuzu Central Hospital pediatric ward A- Nursery. The study will have a sample size of 15 mothers and data will be collected using a questionnaire. The data will be analysed using a content analysis method.